Use of cyclostationary properties of vibration signals to identify gear wear mechanisms and track wear evolution. (March 2021) - Feng, Ke; Smith, Wade A.; Borghesani, Pietro; Randall, Robert B.; Peng, Zhongxiao
Highlights: A vibration-based wear mechanism identification procedure is proposed. Wear evolution is tracked using an indicator of vibration cyclostationarity (CS). The correlation between surface features and vibration characteristics is investigated. Methods validated using lubricated and dry gear wear tests. Abstract: Fatigue pitting and abrasive wear are the most common wear mechanisms in lubricated gears, and they have different effects on the gear transmission system. To develop effective methods for online gear wear monitoring, in this paper, a vibration-based wear mechanism identification procedure is proposed, and then the wear evolution is tracked using an indicator of vibration cyclostationarity (CS). More specifically, with consideration of the underlying physics of the gear meshing process, and the unique surface features induced by fatigue pitting and abrasive wear, the correlation between tribological features of the two wear phenomena and gearmesh-modulated second-order cyclostationary (CS2) properties of the vibration signal is investigated. Differently from previous works, the carrier frequencies (spectral content) of the gearmesh-cyclic CS2 components are analysed and used to distinguish and track the two wear phenomena. The effectiveness of the developed methods in wear mechanism identification and degradation tracking is validated using vibration data collected in two tests: a lubricated test dominated by fatigue pitting and a dry test dominated by abrasive wear. This development enables vibration-based techniques to be used for identifying and tracking fatigue pitting and abrasive wear.